Gender integration of agricultural innovation: implications for the genetically modified crop product development pipeline - Elizabeth Katz (GM Crops & Food, 2024)
We provide guidance on how to incorporate best practices around gender integration in the development of genetically improved crops by adapting a gender integration framework for conventional crop breeding to the GM product development pipeline, which places greater emphasis on the discovery and launch phases because the technical nature of the development process means fewer opportunities for farmer engagement or pivoting possibilities between these two ends of the product development spectrum. For crop innovation to be relevant to both women and men producers, during the discovery phase, developers can conduct baseline gender analysis consisting of gender-disaggregated value chain analysis, systematic learning about gender-specific crop trait preferences, and identification of varietal preferences by women and men along the value chain. The latter opportunity in the GM product development pathway for intentional gender integration is deployment, including pre-launch activities such as field demonstrations and consumer testing. We also describe ex ante and ex post gender impact assessment methods. We conclude with a number of gender integration recommendations for GM product developers: improving gender data collection and analysis to inform crop innovation efforts, investing in staffing and training of scientific teams to enhance gender expertise, and increasing accountability of product development teams with gender-intentional monitoring and evaluation systems.